经皮冷冻猪肺的影像学和病理学研究 (Zhongguo Fei Ai Za Zhi, 2010)
BACKGROUND AND OBJECTIVE: Lung cancer is one of the most commonly occurring malignancies and frequent causes of death in the world. Cryoablation is a safe and alternative treatment for unresectable lung cancer. Due to the lung being gas-containing organ and different from solid organs such as liver and pancreas, it is difficult to achieve the freezing range of beyond the tumor edge 1 cm safety border. The aim of this study is to examine the effect of different numbers of freeze cycles on the effectiveness of cryoablation on normal lung tissue and to create an operation guideline that gives the best effect. METHODS: Six healthy Tibetan miniature pigs were given a CT scan and histological investigation after percutaneous cryosurgery. Cryoablation was performed as 2 cycles of 10 min of active freezing in the left lung; each freeze followed by a 5 min thaw. In the right lung, we performed the same 2 cycles of 5 min of freezing followed by 5 min of thawing. However, for the right lung, we included a third cycle of consisting of 10 min of freezing followed by 5 min of thawing. Three cryoprobes were inserted into the left lung and three cryoprobes in the right lung per animal, one in the upper and two in the lower lobe, so as to be well away from each other. Comparison under the same experimental condition was necessary. During the experiment, observations were made regarding the imaging change of ice-ball. The lungs were removed postoperatively at 3 intervals: 4 h, 3 d of postoperation and 7 d of postoperation, respectively, to view microscopic and pathological change. RESULTS: The ice-ball grew gradually in relation to the increase in time, and the increase in number of cycles. The size of the cryolesion (hypothesis necrotic area) in specimens, over time, became larger in size than the size of the ice-ball during operation, regardless of whether 2 or 3 freeze-thaw cycles were performed. The area of necrosis was gradually increased over the course of time. The hypothesis necrotic area was equal to necrosis area 3 d after cryosurgery. CONCLUSION: Percutaneous cryoablation of the lung can achieve complete ablation of target tissue. The freezing technique may be different depending on the individual circumstances of each tumor. In technology, 3 freeze-thaw cycles are recommended, and the range of cryoablation's effective diameter may be not necessarily beyond the tumor edge at least 1 cm safe border during cryosurgery.